Diagnostic value of qualitative and strain ratio elastography in the differential diagnosis of non‐palpable testicular lesions. (27th August 2016) - Pozza, C.; Gianfrilli, D.; Fattorini, G.; Giannetta, E.; Barbagallo, F.; Nicolai, E.; Cristini, C.; Di Pierro, G. B.; Franco, G.; Lenzi, A.; Sidhu, P. S.; Cantisani, V.; et al.
Summary: The purpose of this study was to evaluate prospectively the accuracy of qualitative and strain ratio elastography (SE) in the differential diagnosis of non‐palpable testicular lesions. The local review board approved the protocol and all patients gave their consent. One hundred and six patients with non‐palpable testicular lesions were consecutively enrolled. Baseline ultrasonography (US) and SE were correlated with clinical and histological features and ROC curves developed for diagnostic accuracy. The non‐palpable lesions were all ≤1.5 cm; 37/106 (34.9%) were malignant, 38 (35.9%) were benign, and 31 (29.2%) were non‐neoplastic. Independent risk factors for malignancy were as follows: size (OR 17.788; p  = 0.002), microlithiasis (OR 17.673, p  < 0.001), intralesional vascularization (OR 9.207, p  = 0.006), and hypoechogenicity (OR, 11.509, p  = 0.036). Baseline US had 89.2% sensitivity (95% CI 74.6–97.0) and 85.5% specificity (95% CI 75.0–92.8) in identifying malignancies, and 94.6% sensitivity (95% CI 86.9–98.5) and 87.1% specificity (95% CI 70.2–96.4) in discriminating neoplasms from non‐neoplastic lesions. An elasticity score (ES) of 3 out of 3 (ES3, maximum hardness) was recorded in 30/37 (81.1%) malignant lesions ( p  < 0.001). An intermediate score of 2 (ES2) was recorded in 19/38 (36.8%) benign neoplastic lesions and in 22/31 (71%) non‐neoplastic lesions ( p  = 0.005 and p  = 0.001 vs. malignancies). None of the non‐neoplastic lesions scored ES3. Logistic regression analysis revealed a significant association between ES3 and malignancy (χ 2  = 42.212, p  < 0.001). ES1 and ES2 were predictors of benignity ( p  < 0.01). Overall, SE was 81.8% sensitive (95% CI 64.8–92.0) and 79.1% specific (95% CI 68.3–88.4) in identifying malignancies, and 58.6% sensitive (95% CI 46.7–69.9) and 100% specific (95% CI 88.8–100) in discriminating non‐neoplastic lesions. Strain ratio measurement did not improve the accuracy of qualitative elastography. Strain ratio measurement offers no improvement over elastographic qualitative assessment of testicular lesions; testicular SE may support conventional US in identifying non‐neoplastic lesions when findings are controversial, but its added value in clinical practice remains to be proven.